Connexin30-Deficiency Causes Mild Hearing Loss With the Reduction of Endocochlear Potential and ATP Release - Chen, Junmin; Chen, Penghui; He, Baihui; Gong, Tianyu; Li, Yue; Zhang, Jifang; Lv, Jingrong; Mammano, Fabio; Hou, Shule; Yang, Jun (Frontiers in Cellular Neuroscience, 2022)
GJB2 and GJB6 are adjacent genes encoding connexin 26 (Cx26) and connexin 30 (Cx30), respectively, with overlapping expression in the inner ear. Both genes are associated with the commonest monogenic hearing disorder, recessive isolated deafness DFNB1. Cx26 plays an important role in auditory development, while the role of Cx30 in hearing remains controversial. Previous studies found that Cx30 knockout mice had severe hearing loss along with a 90% reduction in Cx26, while another Cx30 knockout mouse model showed normal hearing with nearly half of Cx26 preserved. In this study, we used CRISPR/Cas9 technology to establish a new Cx30 knockout mouse model (Cx30-/-), which preserves approximately 70% of Cx26. We found that the 1, 3, and 6-month-old Cx30-/- mice showed mild hearing loss at full frequency. Immunofluorescence and HE staining suggested no significant differences in microstructure of the cochlea between Cx30-/- mice and wild-type mice. However, transmission electron microscopy showed slight cavity-like damage in the stria vascularis of Cx30-/- mice. And Cx30 deficiency reduced the production of endocochlear potential (EP) and the release of ATP, which may have induced hearing loss. Taken together, this study showed that lack of Cx30 can lead to hearing loss with approximately 30% reduction of Cx26 in present Cx30 knockout model. Hence, Cx30 may play an important rather than redundant role in hearing development.